Age and Growth of Striped Venus Clam Chamelea gallina (Linnaeus, 1758) in the Mid-Western Adriatic Sea: A Comparison of Three Laboratory Techniques - Bargione, Giada; Vasapollo, Claudio; Donato, Fortunata; Virgili, Massimo; Petetta, Andrea; Lucchetti, Alessandro (Frontiers in Marine Science, 2020)
Age and growth studies provide critical data for clam fishery management. Three ageing techniques, thin sections and acetate peel replicas – which involve shell sectioning – and surface growth rings were used to estimate the age and growth of Chamelea gallina populations in the mid-western Adriatic Sea. Their results were compared to identify the most reliable and least time-consuming approach. There were no significant differences between the two shell sectioning techniques (χ2 = 4.66, df = 3, p = 0.198), which were described by the same von Bertalanffy (VBF) growth curve parameters (L∞ = 43.9, k = 0.26, t0 = -0.84), whereas significantly different L∞ and k values were found between the two shell sectioning techniques and surface growth rings (L∞: χ2 = 13.62, df = 1, p < 0.001; k: χ2 = 9.18, df = 1, p < 0.002; these statistics refer to the comparison between acetate peels and surface growth rings).The latter approach proved unreliable and error-prone, as it underestimated age and overestimated the growth rate (L∞ = 26.4, k = 1.91, t0 = - 0.11). Although the thin sections and acetate peel techniques both provide reliable age and growth estimates, the former approach was less time-consuming. Our analyses demonstrated that shell growth is slower in the cold season and in older specimens and that it has slowed down over the past few decades.